2007
DOI: 10.1002/pssc.200674837
|View full text |Cite
|
Sign up to set email alerts
|

Growth of highly resistive Ga‐polar GaN by LP‐MOVPE

Abstract: Electrical characteristics of 1.3 µm thick GaN films were investigated with respect to the polar type. Unintentionally doped N-polar GaN grown on nitrided sapphire substrates had a hexagonal facetted morphology and consistently exhibited a high n-type conductivity with a sheet resistance of ~10 Ω/sq, corresponding to a carrier concentration on the order of 10 19 cm -3 . In contrast, Ga-polar GaN films grown on low temperature AlN buffer layers showed a high sheet resistance of ~109 Ω/sq. GaN films of mixed pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The growth process was performed as follows: after the substrate treatments consisting of H 2 annealing at 1100°C for 7 min and nitridation at 940°C for 4 min, a 10 nm thick AlN NL was grown at 600°C and then annealed at the GaN growth temperature of 1050°C in order to obtain highly resistive Ga-polar film. 19,20 After the annealing process, GaN growth was carried out under two different diluent gases, either N 2 or H 2 . A V/III ratio of 100 was established by flowing 36 mol/ min of TEG and 0.4 slm ͑li-ters per minute at standard temperature and pressure͒ of ammonia under a total flow rate of 7.5 slm.…”
Section: Methodsmentioning
confidence: 99%
“…The growth process was performed as follows: after the substrate treatments consisting of H 2 annealing at 1100°C for 7 min and nitridation at 940°C for 4 min, a 10 nm thick AlN NL was grown at 600°C and then annealed at the GaN growth temperature of 1050°C in order to obtain highly resistive Ga-polar film. 19,20 After the annealing process, GaN growth was carried out under two different diluent gases, either N 2 or H 2 . A V/III ratio of 100 was established by flowing 36 mol/ min of TEG and 0.4 slm ͑li-ters per minute at standard temperature and pressure͒ of ammonia under a total flow rate of 7.5 slm.…”
Section: Methodsmentioning
confidence: 99%
“…A second ammonia‐annealing step for 11 min under an ammonia partial pressure of 10 Torr was performed prior to the GaN film growth. It was previously observed that the corresponding GaN films grown without performing these last two steps in the described way had properties of mixed‐polarity films 11. The GaN film was grown to a thickness of 1.3 µm followed by a 50 nm thick Si:GaN film for the channel.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that growth pressure has a great impact on the GaN buffer resistivity in MOVPE technology of AlGaN/GaN heterostructures. [20][21][22][23] We have checked whether it is possible to decrease 2DEG's resistivity while maintaining good insulation of GaN buffer at higher growth pressures.…”
Section: Doi: 101002/crat202100090mentioning
confidence: 99%